2014
DOI: 10.1111/jan.12580
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative systematic review: barriers and facilitators to smoking cessation experienced by women in pregnancy and following childbirth

Abstract: Aim. To explore barriers and facilitators to smoking cessation experienced by women during pregnancy and postpartum by undertaking a synthesis of qualitative studies. Background. The majority of pregnant women are aware that smoking in pregnancy compromises maternal and infant health. Despite this knowledge, quit rates among pregnant women remain low, particularly among women in disadvantaged circumstances; disadvantage also increases the chances of living with a partner who smokes and returning to smoking aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
155
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(165 citation statements)
references
References 58 publications
(262 reference statements)
10
155
0
Order By: Relevance
“…Midwives’ tendency to promote reduction over abstinence is also found outside of the United Kingdom (Flemming et al ., 2016; Glover et al ., 2008), although likely reasons for this have not before now been described. Promoting reduction over abstinence can increase ambivalence and reduce motivation to quit for some women (Flemming et al ., 2015; Naughton et al ., 2013), although others report it as supportive as it recognizes the difficulty they have in stopping smoking (Flemming et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midwives’ tendency to promote reduction over abstinence is also found outside of the United Kingdom (Flemming et al ., 2016; Glover et al ., 2008), although likely reasons for this have not before now been described. Promoting reduction over abstinence can increase ambivalence and reduce motivation to quit for some women (Flemming et al ., 2015; Naughton et al ., 2013), although others report it as supportive as it recognizes the difficulty they have in stopping smoking (Flemming et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…This view prevails in the United Kingdom despite near universal provision of NRT to pregnant women in the SSSs (Fahy, Cooper, Coleman, Naughton, & Bauld, 2014). It is no surprise, therefore, that pregnant women are uncertain about the safety of NRT in pregnancy (Flemming et al ., 2015) and some perceive the risks of NRT to be equal to tobacco (Naughton et al ., 2013). This may extend to new nicotine‐containing devices such as e‐cigarettes, which, unlike NRT, are not licensed as medicines (Oncken et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent synthesis of 38 studies, including 1100 pregnant women, found living with a partner who smoked increased the likelihood of smoking post birth. Additionally, women whose partners did not challenge their smoking were found to smoke one year post birth [38,39]. Women's smoking issues should be considered alone rather than as a couple [25] as tobacco reduction interventions in pregnancy may cause conflict between a woman and a partner.…”
Section: Discussionmentioning
confidence: 99%
“…Further effect factors, such as the individual stresses of pregnancy, the functionality of the consumption, the consumption and support behaviour in the social context, financial aspects or the individual degree of motivation additionally influence the utilisation of internet based counselling [33][34][35]. Greater attention should therefore be given to these aspects when designing programmes for the target group of pregnant women consuming addictive substances.…”
Section: Comparative Studiesmentioning
confidence: 99%